Spatiotemporal Tracking of Cells in Tissue Engineered Cardiac Organoids - Iyer, Rohin K. (2009)
Cardiac tissue engineering aims to create myocardial patches for repair of defective or damaged native heart muscle. The inclusion of non-myocytes in engineered cardiac tissues has been shown to improve the properties of cardiac tissue compared to tissues engineered from enriched populations of myocytes alone. While attempts to mix non-myocytes (fibroblasts, endothelial cells) with cardiomyocytes have been made, very little is understood about how the tissue properties are affected by varying the respective ratios of the three cell types and how these cells assemble into functional tissues with time. The goal of this study was to investigate the effects of modulating the ratios of the three cell types as well as to spatially and temporally track cardiac tri-cultures of cells. Primary neonatal cardiac fibroblasts and D4T endothelial cells were incubated in 5µM of CellTracker™ Green dye and CellTracker™ Red dye respectively while neonatal cardiomyocytes were labeled with 20µg/mL of DAPI. The non-myocytes were seeded either sequentially (Pre-culture) or simultaneously (Tri-culture) in Matrigel-coated microchannels and allowed to form organoids, as in our previous studies. We also varied the seeding percentage of cardiomyocytes while keeping the total cell number constant in an attempt to improve the functional properties of the organoids. Organoids were imaged on days 1 and 4. Endothelial cells were seen to aggregate into clusters when Simultaneously Tri-cultured with myocytes and fibroblasts, while Pre-cultures contained elongated cells. Functional properties of organoids were improved by increasing the seeding percentage of enriched cardiomyocytes from 40% to 80%.